2008
DOI: 10.1016/j.rmed.2007.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Reduced number and activity of circulating endothelial progenitor cells in patients with idiopathic pulmonary arterial hypertension

Abstract: Our observations indicated that EPC numbers and functional capacity were impaired in patients with IPAH, which might not only give potential insight into the pathophysiological mechanisms but also might be useful for identifying suitable therapeutic targets in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
93
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 49 publications
8
93
1
Order By: Relevance
“…A volume of 100 μl of peripheral blood was obtained and incubated for 30 min at 4 °C with antihuman-KDR-PE (R&D Systems, Minneapolis, USA) and antihuman-AC133-APC (eBioscence, San Diego, USA). The suspension was collected and incubated with fluorescence-activated cell sorter (FACS) lysing solution for 10~15 min Zhu et al, 2008). FACS-Calibur instrument (Becton-Dickson, New Jersey, USA) was used to analyze cell surface marker proteins.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…A volume of 100 μl of peripheral blood was obtained and incubated for 30 min at 4 °C with antihuman-KDR-PE (R&D Systems, Minneapolis, USA) and antihuman-AC133-APC (eBioscence, San Diego, USA). The suspension was collected and incubated with fluorescence-activated cell sorter (FACS) lysing solution for 10~15 min Zhu et al, 2008). FACS-Calibur instrument (Becton-Dickson, New Jersey, USA) was used to analyze cell surface marker proteins.…”
Section: Flow Cytometry Analysismentioning
confidence: 99%
“…Several clinical studies have also demonstrated that hypoadiponectinemia correlated with endothelial dysfunction in peripheral arteries and CAD (Iwashima et al, 2006a;2006b; Journal of Zhejiang University SCIENCE B ISSN 1673-1581 (Print); ISSN 1862-1783 (Online) www.zju.edu.cn/jzus; www.springerlink.com E-mail: jzus@zju.edu.cn Otake et al, 2008). Endothelial dysfunction is an early pivotal event in the development, progression, and manifestation of atherosclerosis and ultimately represents an imbalance between the magnitude of injury process and repair capacity (Zhu et al, 2008). Previous studies suggested that circulating endothelial progenitor cells (EPCs) participate in this endothelial repair process (Hill et al, 2003;Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations